Impact of Impulse and Impact Force: An Innovative Approach to Teaching Momentum in Physics - Taufik, Muhammad; A, Syahrial (Mataram University, 2024)
Momentum is a fundamental concept in physics that is pivotal for understanding the motion and behavior of objects. However, its abstract nature often makes it challenging for students to grasp. This study investigates an innovative teaching approach that incorporates impulse and impact force as tools to enhance students' comprehension of momentum. Drawing from the pedagogical philosophy of Prof. Yohannes Surya, who emphasizes practical application and interactive learning, we implemented a set of interactive demonstrations and problem-solving exercises to teach the concepts of impulse and impact force. This study was conducted in the Basic Physics course for the Biology Education Program at Mataram University. The results indicate that emphasizing impulse and impact force improves student understanding, enhances engagement, and bridges the gap between theory and real-world applications in physics education. The findings support the integration of hands-on activities and experiential learning as effective pedagogical strategies in teaching classical mechanics